A Lexicologia no Brasil (1960-2000): historiografia de sua origem, desenvolvimento e institucionalização - Butti, Cassiano (2024)
The proposed thesis is part of the History and Description of the Portuguese Language line of research at Pontifícia Universidade Católica de São Paulo (PUC-SP) and its theme is the process of institutionalization of Lexicology in the second half of the 20th century, more specifically between the years 1960-2000. The study is justified by the lack of academic papers that analyze, from a historiographical perspective, events on the reception, development and institutionalization of Lexicology in the history of Brazilian linguistics. The general objective of the investigation, therefore, is to understand how Lexicology was perceived, received and proposed in Brazil, in the second half of the 20th century. The specific objectives are: 1) to (re)construct an interpretative historiographical narrative about the origin, development and institutionalization of Lexicology in the European scenario – geographical space where this discipline was conceived; 2) to map the documentary sources and historical episodes that highlight the process of consolidation of modern Lexicology as an academic-scientific discipline; 3) to analyze, in light of the theoretical-methodological principles of the Historiography of Linguistics, how lexicological studies were implemented, developed and institutionalized in the Brazilian academic scenario, in a synchronic period limited to the years 1960 to 2000; 4) to evaluate, through the interpretative categories of the Historiography of Linguistics, which linguistic[1]lexicological ideas of European origin were continued or discontinued in the time frame in focus, so that the existence of a Brazilian school of Lexicology can be postulated. The research is guided by the hypothesis that Brazilian Lexicology, initially marked by the continuity of European models of structural description, has migrated to an interdisciplinary and discursive perspective. As methodological procedures, the external and internal parameters of historiographical analysis are considered, in which the Koerner's principles of contextualization, immanence and adequacy are presupposed. The theoretical foundations are those oriented in the Historiography of Linguistics, taking as main references the studies of Konrad Koerner, Pierre Swiggers, Cristina Altman and Ronaldo Batista. We opted for documentary research, guided by the following interpretative categories: external and internal reconstruction; reception of ideas; specialty groups; intellectual leadership and organizational leadership; research program; continuities and discontinuities. The research shows that Brazilian Lexicology was institutionalized in the 20th century as an area of linguistic science and an autonomous academic discipline that deals with the observation, analysis, description and explanation of lexical phenomena that typify Brazilian Portuguese in terms of its history, structure, content, functions and uses